2006
DOI: 10.1002/cjoc.200690296
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Novel Chiral α‐Aminophosphonates Containing Fluorine Moiety

Abstract: Chiral α-aminophosphonates were synthesized using (R) or (S)-1-phenylethylamine in the presence of BF 3 •Et 2 O under microwave irradiation in moderate to good yields. The new compounds were identified by 1 H NMR, 19 F NMR, IR and elemental analysis. Their antifungal activities were evaluated and some compounds were found to exhibit excellent antifungal activities. To the best of our knowledge, this is the first report on antifungal activity of chiral α-aminophosphonates containing fluorine moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 17 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…The bioassay results showed that the racemate possessed good antiviral and antitumor activities. [36][37][38][39][40] As different chiral aminophosphonates and their derivatives display varying bioactivities, screening of fluorine derivatives bearing a-amiophosphonate moieties might lead to new antiviral agent with more potent antiviral activities. Keeping these considerations in mind, herein a series of new fluorine containing bioactive chiral a-aminophosphonates were asymmetrically synthesized using chiral Bronsted acid organocatalyst 3 7,41-45 derived from (R)-or (S)-BINOL 46 in a typical hydrophosphonylation reaction of aldimines obtained from cinnamaldehyde and fluorinated aromatic amine with dialkyl phosphites.…”
Section: Introductionmentioning
confidence: 99%
“…The bioassay results showed that the racemate possessed good antiviral and antitumor activities. [36][37][38][39][40] As different chiral aminophosphonates and their derivatives display varying bioactivities, screening of fluorine derivatives bearing a-amiophosphonate moieties might lead to new antiviral agent with more potent antiviral activities. Keeping these considerations in mind, herein a series of new fluorine containing bioactive chiral a-aminophosphonates were asymmetrically synthesized using chiral Bronsted acid organocatalyst 3 7,41-45 derived from (R)-or (S)-BINOL 46 in a typical hydrophosphonylation reaction of aldimines obtained from cinnamaldehyde and fluorinated aromatic amine with dialkyl phosphites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the antibacterial activity of α-aminophosphonates has been reported in the literature against gram-positive and gram-negative bacteria, [9][10][11][12] but the new synthesized compounds in this paper had MIC more than 256 µg/ ml against the investigated bacteria. It has been reported that pharmacological effects of α-aminophosphonates are sterospecific; [8] therefore, we suggest that antibacterial effect of these compounds may be stereoselective and the antibacterial evaluation of each enantiomer separately can confirm this matter.…”
Section: Antimicrobial Assaymentioning
confidence: 75%
“…[1][2][3][4][5] It has been reported that some alkyl-substituted phosphonate compounds have antifungal activity, [7,8] antibacterial activity, [9][10][11][12] antitumor effects [13][14][15] and antiviral activity. [16] Also, the activities of α-aminophosphonates as peptidomimetics, [17] enzyme inhibitors, [18] haptens of catalytic antibodies, [19] herbicidals, [20] inhibitors of serine hydrolases [21] and inhibitors of UDP-galactopyranose mutase [22] are reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…100 µg/mL) was added to sterilized Czapek media (0.2 % NaNO 3 , 0.131 % K 2 HPO 4 ·3H 2 O, 0.05 % KCl, 0.05 % MgSO 4 ·7H 2 O, 0.00183 % FeSO 4 ·7H 2 O, 3 % sucrose, pH 6.8) [17] in which F. oxysporum had incubated for a few days. After incubating together at 27 o C for 24 h, it was observed under microscope (Olympus 800 ×).…”
Section: Hyphal Morphology Of F Oxysporummentioning
confidence: 99%